2020
DOI: 10.3389/fmed.2020.535902
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Bone Marrow Mononuclear Cells Transplantation Improves the Effect of Training in Chronic Stroke Mice

Abstract: There is no effective treatment for chronic stroke if the acute or subacute phase is missed. Rehabilitation alone cannot easily achieve a dramatic recovery in function. In contrast to significant therapeutic effects of bone marrow mononuclear cells (BM-MNC) transplantation for acute stroke, mild and non-significant effects have been shown for chronic stroke. In this study, we have evaluated the effect of a combination of BM-MNC transplantation and neurological function training in chronic stroke. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In the conditioning phase, a mild electric foot shock was administered 10 s after each mouse crossed the adjacent dark compartment and door closing. On the next day, each mouse was again placed in the illuminated compartment and habituated for 10 s, and the time to cross over to the dark compartment after door opening, up to a maximum of 180 s, was recorded as the test phase (Ogawa et al, 2020). The wire hang test evaluates muscular strength or motor function.…”
Section: Bm-mnc Transplantation To Aged Micementioning
confidence: 99%
See 1 more Smart Citation
“…In the conditioning phase, a mild electric foot shock was administered 10 s after each mouse crossed the adjacent dark compartment and door closing. On the next day, each mouse was again placed in the illuminated compartment and habituated for 10 s, and the time to cross over to the dark compartment after door opening, up to a maximum of 180 s, was recorded as the test phase (Ogawa et al, 2020). The wire hang test evaluates muscular strength or motor function.…”
Section: Bm-mnc Transplantation To Aged Micementioning
confidence: 99%
“…In this test, each mouse was placed on the center of wire mesh plate (450 mm × 300 mm; mesh wire was 1.3 mm in diameter and spaced at 12 mm intervals, KK23-8331; Kohnan, Osaka, Japan) and allowed to accommodate to this environment for 5 s. The wire mesh plate was inverted and secured to the top of a cubic transparent open-topped glass box (250 mm × 250 mm × 250 mm). Latency to fall was recorded, up to a maximum of 180 s. This trial was repeated five times with an interval of 1 min and the average time to fall was calculated (Ogawa et al, 2020).…”
Section: Bm-mnc Transplantation To Aged Micementioning
confidence: 99%
“…To assess motor function, mice were subjected to behavioral testing using the wire hang, water maze, and rotarod tests. All behavioral tests were conducted at the optimal time, determined by a preliminary study ( 9 ). Prior to administration of cell therapy, behavior tests were conducted to confirm that there were no significant differences in behavioral disorders among individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it has been argued that stem cells cannot have a therapeutic effect at the chronic stage. However, in our previous study, we demonstrated that combination therapy of training and bonemarrow-derived HSCs had significant therapeutic effects in a murine chronic stroke model (9). Since it has been suggested that it may also have a therapeutic effect in humans, we plan to conduct a human clinical trial of HSC therapy for chronic stroke using G-CSF mobilized autologous peripheral blood CD34 positive (CD34 + ) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, nonclinical studies in rodents and primates, and early clinical studies have investigated the therapeutic potential of various stem cell types revealing MSCs as a promising treatment for stroke [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In all but a few rat studies [32][33][34] and one human safety trial [15,28], the role of MSCs has been studied in an acute model of stroke. Although initially designed as a replacement therapy, MSCs are not thought to replace missing neural circuitry, but rather to act as environmental modi ers, altering the in ammatory landscape of the injured brain (increasing the levels of anti-in ammatory cytokines and growth factors and decreasing the levels of pro-in ammatory cytokines) [21,31].…”
Section: Introductionmentioning
confidence: 99%